2016
DOI: 10.1111/cico.12189
|View full text |Cite
|
Sign up to set email alerts
|

“It's Not Just a Bunch of Buildings”: Social Psychological Investment, Sense of Community, and Collective Efficacy in a Multiethnic Low–Income Neighborhood

Abstract: This analysis of social life in a poor, multiethnic public housing neighborhood presents an opportunity for refinement of social disorganization theory. Drawing on data from interviews, focus groups, and participant observations among residents, I find that this neighborhood exhibits substantial collective efficacy, despite social disorganization theory's predictions that the structural conditions of high poverty and racial and ethnic diversity result in low collective efficacy. I explicate two social psycholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 73 publications
(125 reference statements)
1
16
0
2
Order By: Relevance
“…In addition, since the homeowners who perceive their neighbourhood as a good place to live are far more likely to initiate and participate in do-it-yourself activities in maintenance [67], reaching a higher dwelling quality in large housing estates may also provide benefits in terms of residents' attitude towards further maintenance and their motivation to preserve the upgraded living environment. In relation to this, some researches emphasize the role of sense of community, neighbourhood attachment, collective efficiency [68] and social capital in the rehabilitation process [69].…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…In addition, since the homeowners who perceive their neighbourhood as a good place to live are far more likely to initiate and participate in do-it-yourself activities in maintenance [67], reaching a higher dwelling quality in large housing estates may also provide benefits in terms of residents' attitude towards further maintenance and their motivation to preserve the upgraded living environment. In relation to this, some researches emphasize the role of sense of community, neighbourhood attachment, collective efficiency [68] and social capital in the rehabilitation process [69].…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Here, the article identifies a new connection between local property institutions and collective efficacy. Previous studies have found that collective efficacy is positively associated with individual homeownership (Sampson 2012), and with the sense of ownership that gardening instills in renters (Walton 2016). These studies suggest that individual ownership, or simply a sense of ownership, helps foster neighborhood collective efficacy.…”
mentioning
confidence: 64%
“…This supports the study hypothesis that neighbourhoods' shrinkage can lead to a stronger desire for community cohesion and for the spaces that might reinforce social interaction. This increased social interaction, potentially conducive to higher levels of social capital and collective efficacy, can, in turn, reinforce the processes of neighbourhood safety and upkeep, with positive consequences in place attachment and potentially in neighbourhood desirability [16,[19][20][21], although community attachment alone, according to Mahmoudi Farahani [58], can be an enhancing factor for a sense of safety, identity, participation, mental health, and wellbeing.…”
Section: Discussionmentioning
confidence: 99%
“…This type of social relationship is the basis for good levels of social capital as well as collective efficacy at the neighbourhood level, that is, a strong social network of trust and mutual aid [15] that can, in turn, lead to a strong capacity to work together for a common good/objective that can better serve the community at stake [16][17][18]. This capacity to work together for a common good-collective efficacy-will enhance levels of order and upkeep [19], which are considered two of the five key factors for the image of a city for the public, according to Nasar [20], and place attachment [21]. Collective efficacy is also positively associated with lower levels of violence [22] and crime [23], a problem reported in several depopulating neighbourhoods [24].…”
Section: Introduction: Friendly Communities In Depopulating Urban Conmentioning
confidence: 99%